Leader Psychological Need Satisfaction Trickles Down: The Role of Leader-Member Exchange - Decuypere, Anouk; Bauwens, Robin; Audenaert, Mieke (Frontiers in Psychology, 2022)
This article addresses the impact of leader psychological need satisfaction on employees. We draw on Self-Determination Theory (SDT) and Leader-Member-Exchange (LMX) theory to investigate if and how leader psychological need satisfaction trickles down to employee psychological need satisfaction. Adopting a multi-actor, multilevel design, results from 1036 leader-employee dyads indicate that employee-rated LMX mediates the trickle-down effect of leader psychological need satisfaction. Additional analyses of leader psychological needs show that leader competence is the main psychological need that underlying this relationship. We also found an unexpected negative association between leader autonomy need satisfaction and employee competence need satisfaction. Overall, this study shows the importance of both (1) leaders’ psychological need satisfaction and (2) employee perceptions of the relationship quality for employee psychological need satisfaction.